The factors that create a successful mobile money ecosystem: Kenya vs Nigeria - Finlay, Peter (Research of GSB, 2018)
This study set out to investigate factors affecting the adoption of mobile money services in Kenya and Nigeria. Using various models such as; the Technology Acceptance Model (TAM), Unified Technology Acceptance User Theory (UTAUT), Innovation Diffusion Process and demographic variables (age, sex, education level, access bank account, ownership of mobile phone, MM awareness) from datasets produced by Financial Inclusion Insights. This survey data is nationally representative for Nigeria with a sample of 6,001 adults aged 15 or older, both male and female and Kenya with a sample of 2,994 adults aged 15 or older, both male and female. The study employed the probit and logit regression model to examine the significant determining factors of mobile money adoption in Kenya and Nigeria. The results of the analysis revealed that the average respondent of the populations in both markets has access to a mobile phone and hence technology is not a limiting factor to the penetration of Mobile Money in both these markets. The primary limiting factor is due to low levels of financial education, literacy and access to microfinance. The average Nigerian respondent did not know about Mobile Money whereas the average Kenyan respondent knew something about Mobile Money. Additionally, in Kenya, the MM initiative was privately led by MNO's where in Nigeria the Central Bank controls the MM industry. From the logit and probit results, the study identifies that the following variables; (FF1) personally registered a bank account, (MM1) has the respondent heard of Mobile Money were significant determinants of MMU in Nigeria. While in Kenya; (DG1) age of respondent, (MM1) has the respondent heard of something called mobile money, (FF1) personally registered bank account were the significant determining factors affecting MMU. This study has therefore shown that, despite the lower penetration and absorption of mobile money services in Nigeria, factors that create a thriving MM ecosystem like that in Kenya are obtainable in Nigeria. If the Nigerian regulators were to change the political and financial framework and create a more accessible market Nigeria could look a lot like Kenya's MM ecosystem.